Mixture Condensation of Ethanol/Water and Ethanol/Siloxane in a Vertical Double Pipe. Issue 5 (17th February 2023) - Zimmermann, Conrad; Lubos, Nico; Dagli, Cagatay Necati; Kabelac, Stephan
Abstract: Eco‐friendly mixtures may substitute pure working fluids in thermodynamic cycle processes, yet the existing calculation approaches of mixture condensation are complex due to iterative procedures and multiple input data. To simplify condenser design, this project aims for a new calculation method of mixtures. On this behalf, experimental data for the condensation of ethanol/water and ethanol/octamethyltrisiloxane is provided within a wide composition range to identify the most influential parameters. Finally, a practical prediction method for heat transfer coefficients of mixtures is suggested. Abstract : Experimental data is presented for mixture and pure fluid condensation within a wide composition range. Influential parameters for the heat transfer deterioration of mixtures are discussed. The results enable an explicit calculation of condensation heat transfer coefficients depending on the mixture composition.